Physiological and biochemical study of the effect of Anxiety exam in the blood of students. - Mustafa Ali Abdulrahman; M. Adnan Telfah Mohmed; Raghad Mohammed Abdul Rahman (Tikrit Journal of Pure Science)
This study was conducted on the students of the Faculty of Education / University of Samarra, Department of biology  for the period of (10/ 11/ 2010 to 28/02/2011 ) study were divided into two groups only . Set before performing the exam results were compared to a group before the exam results with a group after the exam.